2013
DOI: 10.1371/journal.pmed.1001496
|View full text |Cite
|
Sign up to set email alerts
|

Towards Universal Voluntary HIV Testing and Counselling: A Systematic Review and Meta-Analysis of Community-Based Approaches

Abstract: In a systematic review and meta-analysis, Amitabh Suthar and colleagues describe the evidence base for different HIV testing and counseling services provided outside of health facilities. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
343
5
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(377 citation statements)
references
References 140 publications
(244 reference statements)
27
343
5
2
Order By: Relevance
“…Due to the poor health seeking behaviors of men, majority of men present to the health facilities when they are sick (HIV related) and through PITC, a significant proportion of them test positive for HIV, hence higher positivity rates. This is supported by findings by Suthar et al (2013) who found out that health facility based HTC positivity rates were higher than the community based rates. This was due to the fact that symptomatic people with HIV are more likely to visit health facilities than healthy people (Suthar et al, 2013).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Due to the poor health seeking behaviors of men, majority of men present to the health facilities when they are sick (HIV related) and through PITC, a significant proportion of them test positive for HIV, hence higher positivity rates. This is supported by findings by Suthar et al (2013) who found out that health facility based HTC positivity rates were higher than the community based rates. This was due to the fact that symptomatic people with HIV are more likely to visit health facilities than healthy people (Suthar et al, 2013).…”
Section: Discussionsupporting
confidence: 66%
“…This is supported by findings by Suthar et al (2013) who found out that health facility based HTC positivity rates were higher than the community based rates. This was due to the fact that symptomatic people with HIV are more likely to visit health facilities than healthy people (Suthar et al, 2013). In a study by Kyaddondo et al (2012) in Eastern Uganda, most respondents considered HTC in their own homes as more private than in health facilities.…”
Section: Discussionsupporting
confidence: 66%
“…'Targeted' HIV testing in combination with community-level HIV testing might also be considered, especially in the light of the prevailing low and concentrated HIV epidemic in the country. 26 Second, the highly Ebola-affected counties need special attention in terms of support and proportionate distribution of resources to accelerate recovery. These counties may be further grouped based on population and individual HIV testing rates and require more intense review to understand the reasons for low post-outbreak HIV testing rates.…”
Section: Public Health Action Ebola Outbreak and Hiv Testing In Libermentioning
confidence: 99%
“…Though logistically intensive, HTC is feasible, acceptable, and effective at achieving high coverage at the population level. 7 Many programmes in sub-Saharan Africa, including that described by Ying and colleagues, have very high coverage rates. 8 No other testing approach could diagnose 90% of HIVpositive people more comprehensively.…”
Section: Home Testing and Counselling With Linkage To Carementioning
confidence: 99%